Anti-Aging Face Cream Preparations Made from Collagen Membrane Chicken Eggshell (Gallus gallus domesticus) Combined with Bee Honey (Apis mellifera) - Adinda Fitri Salsabila; Nata Dwi Anisa Nizma; Janahwati, Erma Nur; Amalia, Shofia; Kurniawan, Muhammad Prasetya (Indonesian Journal of Pharmacy, 2022)
Handling waste such as chicken egg shells requires innovation to be able to provide added value as a sustainable product. This study aims to extract collagen from chicken egg shell membranes combined with bee honey as an anti-aging face cream. This material has a very high model accuracy value (97.89%) which has the potential to inhibit aging due to Matrix metalloproteinase-1 (MMP-1). This research was carried out by extracting eggshell membrane collagen, making cream combined with bee honey, analyzing product properties, and interpreting virtual data. The results show that in 100 g of face cream formulation with active ingredients of chicken eggshell membrane collagen extract 4.1206% and bee honey 5.0251%; 77.0926% water; 0.0062% ash; 1,8690% protein; 0.0058% fat, the viscosity value was 65.94 dPas, and the pH was 7.08. Thus, this product did not irritate the skin of the experimental animals. The average value of attribute assessment (such as aroma, consistency, texture, stickiness, homogeneous sensation, color, appearance, itching, erythema, washing power, response after washing) was well received by the panelists with a score of 1-3,9 and the highest total achievement bacteria 25 CFU/g and yeast-mold 16 CFU/g met the skin moisturizer quality requirement (SNI 16-4399-1996) which should not exceed 102 CFU/g.